Co-opting Accessibility: A Critical Look at the Discourse of Higher Education Reform - Richard Wells; Dianne Ramdeholl (Adult Education Research Conference, 2014)
From its beginnings, adult education has been primarily about giving men and women who had been denied by outright discrimination and other structural inequities an opportunity to collectively enrich and empower themselves and their communities by joining a group of scholars and other learners. In other words, adult education has long been linked to struggles around social justice, including the democratization of education itself. Lately, talk of increasing the accessibility of higher education has dropped these broader concerns. Driven in large part by powerful private foundations, we argue that the discourse of reform currently dominating the conversation about the future of higher education is meaningful mainly for the populist cover it provides for a conservative and instrumentalist educational agenda.